EFFECT OF NACL SALINITY ON COTTON (GOSSYPIUM ARBOREUM L.) GROWN ON MS MEDIUM AND IN HYDROPONIC CULTURES - S. Sattar; T. Hussnain; A. Javaid (Journal of Animal and Plant Sciences, 2010)
Salinity is a major environmental stress and is a substantial constraint to cotton production in Pakistan and worldwide. In the present study, cotton (Gossypium arboreum L.) cv. FDH-786 seeds were exposed to different salinity (100, 200, 1000 mM NaCl) levels. In the first experiment, effect of salinity on germination of seeds was observed. Increasing salt concentration resulted in a parallel inhibitory effect on total germination percentage and the rate of germination of cotton seeds. Germination was delayed and significantly reduced by 300-700 mM solution of NaCl. At highest salt levels of 800–1000 mM, germination was completely arrested. The second experiment was conducted to study the effect of different salinity levels on survival of cotton seedlings. The seedlings were grown on MS-medium as well as in hydroponic cultures. Survival percentage was significantly reduced by all the concentrations of the salt solution. Cotton seedlings showed more susceptibility to salt stress in hydroponic cultures than to MS medium. None of the cotton seedlings survived beyond 60 and 40 mM concentration on MS medium and hydroponic cultures, respectively.
Keywords: Cotton; germination; growth; hydroponic cultures; MS medium; salinity